Obesity and sleep in the adult population – a systematic review - Amaral, Odete (2016)
Background Current scientific evidence has reported associations between inadequate sleep patterns and overweight/obesity. Epidemiological studies show a curvilinear relationship in "U-shape" between inadequate sleep and obesity, resulting in consequences on individual and public health levels. Objectives: To identify the association between over- weight/obesity and inadequate sleep patterns among adults. Methods We conducted a systematic review of the literature, using a search in PubMed, Cochrane Library, SciELO and Google Scholar. We identified studies published between January 2008 and November 2015. Inclusion criteria were previously defined, then the selected studies were assessed for their quality and later analysed. By applying the "Scale to critically assess a paper describing a prospective, randomized and controlled clinical trial" in the included studies, it was found that of the four studies that formed the textual corpus, three were considered of quality (final grade ≥ 75 %). Results Inadequate sleep patterns increase the risk of weight gain and consequently of overweight and obesity in adults. This was a result sup- ported by the data presented in the studies analysed (systematic literature review, longitudinal studies of clinical intervention, randomized and controlled trials, cross-sectional analytic studies). Over- weight/obesity are associated with inadequate sleep-wake patterns, namely the "short" duration of sleep in adults. Conclusions An association is suggested between decreased sleep duration and increase in weight. Longitudinal and experimental studies, using objective and repeated measures of sleep, are important to define a causal relationship between sleep deprivation and obesity.